Putative markers for the detection of breast carcinoma cells in blood. - Eltahir, E. M. (Nature Publishing Group, 1998)
The aim of this study was to investigate certain genes for their suitability as molecular markers for detection of breast carcinoma cells using the reverse transcriptase-polymerase chain reaction (RT-PCR). RNA was prepared from MCF-7 breast carcinoma cells and peripheral blood leucocytes of healthy female volunteers. This RNA was screened for mRNA of MUC1, cytokeratin 19 (CK19) and CD44 (exons 8-11) by RT-PCR and the results validated by Southern blots. Variable degrees of expression of MUC1 and CD44 (exons 8-11) were detected in normal peripheral blood, rendering these genes non-specific for epithelial cells and therefore unsuitable for use as markers to detect breast carcinoma cells. Although CK19 mRNA was apparently specific, it was deemed unsuitable for use as a marker of breast cancer cells in light of its limited sensitivity. Furthermore, an attempt at using nested primers to increase sensitivity resulted in CK19 mRNA being detected after two amplification rounds in blood from healthy volunteers. IMAGES: